Failure Depth of a Floor of a Fully Mechanized Working Face When Passing a Collapse Column - Jinlong Cai; Min Tu; Wensong Xu (Advances in Civil Engineering)
The stress change law of a collapse column and the failure depth of a coal seam floor before and after mining when the fully mechanized coal mining face passes through the collapse column are investigated. Here, we present the constructed program in FISH language, render the damage variable in FLAC3D to establish the numerical model, and complete the numerical calculation. The 10–115 working faces that pass the collapse column at a coal mine in Tuanbai are identified as the research object. The floor failure is numerically simulated to assess the damage. The following results were obtained: the failure depth of the full floor is stabilized at 14.6 m; the maximum failure depth of the floor near the collapse column is 18.2 m; and the stress concentration coefficient is 1.27 times greater than that of normal mining. The calculated depth failure of the floor of the working face without structural defects is 14.6–14.7 m based on the Hoek–Brown criterion. With the collapse column, the failure depth of the floor is 16.8–17.8 m. According to the water injection test, the maximum failure depth of the floor is 18 m. The three derived values agree well with one another.